Documenting Death Maternal Mortality and the Ethics of Care in Tanzania - Strong, Adrienne (University of California Press, 2020)
"Documenting Death is a gripping ethnographic account of the deaths of pregnant women in a hospital in a low-resource setting in Tanzania. Through an exploration of everyday ethics and care practices on a local maternity ward, anthropologist Adrienne E. Strong untangles the reasons Tanzania has achieved so little sustainable success in reducing maternal mortality rates, despite global development support. Growing administrative pressures to document good care serve to preclude good care in practice while placing frontline healthcare workers in moral and ethical peril. Maternal health emergencies expose the precarity of hospital social relations and accountability systems, which, together, continue to lead to the deaths of pregnant women. "This powerful and compelling analysis of maternal mortality in rural Tanzania is a groundbreaking addition to scholarship on Africa and its public health challenges. Adrienne E. Strong presents a rich ethnography of hospital function and dysfunction, to which the voices of patients and staff add poignant detail. The ways in which state and global health policy shape maternal health and well-being frame individual narratives in a memorable testimony." Carolyn Sargent, Professor of Anthropology, Washington University in St. Louis Documenting Death is an arresting tale of life and death on a busy maternity ward in rural Tanzania. Drawing on a remarkable period of ethnographic fieldwork, Strong evocatively details the predicament of nurse midwives caught in the 'biobureaucracy' of global health projects and their audit trails. A significant contribution to medical anthropology and critical global health scholarship." Margaret MacDonald, Associate Professor of Anthropology, York University"